Counseling About The Dangers Of Use Of Gadgets On The Social Emotional Development Of Children Aged 6-10 In Denai Lama Village, Kec. Pantai Labu - Dey, Titin Novayanti; Damayanti, Damayanti; Handayani, Dwi; Bintang, Siti Sarah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2023)
Technological developments are very rapid and significant, which is marked by social media that is increasingly widespread and easily accessible. Evidenced by the increasing purchase of gadgets or smartphones, this is in line with the increasing number of gadget users. The use of gadgets that cannot be limited, ranging from children to adults, has an impact not only in a positive but also negative way. According to several data sources, children with excessive use of gadgets can interfere with children's emotional and social development, besides that children with a period of growth and development will experience delays in recent years. The purpose of doing this community service is to educate about the dangers of using Gadgets on the Social Emotional Development of children aged 6-10 years in Denai Lama Village, Pantai Labu District. The community service method is carried out in the form of counseling using a laptop displaying PPT (Power Point Text) data taken using an analytical survey with a Cross-Sectional Study research approach. Results: Of the 35 parent participants (male/mother) who attended, 36.0% of parents knew and were aware of the dangers of using gadgets, 64.0% of parents who did not know and were not aware of the dangers of using gadgets. Conclusion: There are still many parents who do not know and are fully aware of the dangers caused by the use of gadgets for the development of children aged 6-10 years, so education is still needed in the form of counseling and information that is easily accessible to the public.